THE IMPACT OF THE DIGITAL ECONOMY ON THE DEVELOPMENT OF THE WORLD ECONOMY - Avazov, Nuriddin; Maxmudov, Nosir (IJBLE Scientific Publications Community Inc., 2021)
This article analyzes the impact of the digital economy on the development of the world economy. The introduction and development of the concept of digital economy in the economy is also shown. The article also analyzes the advantages of the digital economy and the factors influencing it, and develops proposals and conclusions for the development of the digital economy, studying the research of researchers.